KAJIAN HUKUM PEWARISAN HARTA BENDA TERHADAP ANAK PEREMPUAN YANG SUDAH KAWIN DALAM MASYARAKAT HUKUM ADAT BALI - Nyoman Tri Antika Dewi; landrawan, i wayan; Adnyani, Ni Ketut Sari (Universitas Pendidikan Ganesha, 2024)
Inheritance aims to transfer rights and responsibilities for something material or non-material from one party to another party called the heir. This research aims to (1) determine the position of women in terms of inheritance from the perspective of Balinese Customary Law. (2) To determine the legal consequences of handing over inheritance rights to married women from the perspective of Customary Law in Bali. The type of research used is normative legal research, namely research based on statutory regulations. In this research, a statutory approach is used by examining statutory regulations related to research. The technique for collecting legal materials in this research is using document study techniques, namely by studying data collected from archival research or literature studies such as books, papers, articles, journals, newspapers or the works of legal experts. With this research, it was found that (1) Balinese society is patriarchal, so women are not prioritized in becoming heirs (2) with the Decree of the Main Council of Pakraman Village, Bali Province No: 01/Kep/Psm-3/Mdp Bali/X/2010 Regarding the inheritance of Balinese Hindu women, which has legal force, married women are given inheritance rights to their parents' property.